VIABILITY AND VIGOR TEST OF RICE SEEDS (Oryza sativa, L.) FARMER'S HARVEST RESULTS - Iftitah, Siti Nurul (Universitas Dharmawangsa Medan, 2025)
The study aimed to determine the viability and vigor of rice seeds harvested by farmers. The study was conducted in April 2025 in Pare Kranggan Village, Temanggung, by taking several samples of dry rice harvested by farmers. The samples were dried and then tested for viability and vigor. Each seed was placed in a petri dish containing 100 seeds and replicated three times. This study was designed using a Completely Randomized Design. Observations were made for 14 days, observing seed germination (viability) and seed vigor.The results showed that seeds with a germination rate (viability) above 85% were only obtained from two sample farmers. Seed viability significantly influences the seed vigor index, with seeds with high viability also having a high vigor index. High vigor seeds are indicated by seeds with a high germination rate, namely with a vigor index above 20. One factor influencing low seed viability and vigor is that at harvest, the rice is not yet fully physiologically ripe.